INTERNATIONAL MECHANISMS FOR PROSECUTING ISIL MEMBERS FOR THEIR CRIME OF GENOCIDE AGAINST YAZIDIS PEOPLE IN SINJAR, IRAQ - 2014 INTERNATİONAL CRİMİNAL COURT (ICC) AS A CASE STUDY - OMAR, SAMAN (Journal of Duhok University, 2021)
On August 3, 2014, the terrorist organization Islamic State in Iraq and the Levant (ISIL), also known as Da’esh or most recently shortened to Islamic State (IS) attacked Sinjar in Northern Iraq within the Nineveh province. The region was home to about 400,000 Yazidis as well as other religious minorities. More than two million people have caused serious human rights violations in Nineveh province. ISIL captured Sinjar and the surrounding villages within a few hours on that fateful morning. The Yazidis were specifically targeted by ISIL members and were subjected to some of its worst atrocities including but not limited to executions, sexual slavery, abduction, forced conversion, imprisonment and torture. At the request of the Iraqi government, the United States began conducting air strikes and air-dropping humanitarian aid on August 8, 2014. Between August 9 and 13, Kurdish forces opened a safe corridor, allowing most of the surviving Yazidis to flee through Syria into the Kurdistan region of Iraq. The Rome Statute of the International Criminal Court (ICC) expressly incorporates the court has jurisdiction in accordance with this Statute with respect to the crimes of (a) Genocide; (b) Crimes against humanity; (c)War crimes; (d) The crime of aggression. These are elaborated on in Articles 5 and genocide specifically in Article 6. This study aims to find out whether such heinous international crimes committed by IS against the Yazidi people in Sinjar, Iraq during 2014-2017 can be placed under the jurisdiction of the ICC in accordance with its governing document, the Rome Statute. The study is illustrative and uses a content analysis approach to answer research questions. The researcher analyzed the existing literature as well as the ICC legal documents to interpret and determine the jurisdiction of the ICC regarding the Yazidi genocide in Iraq to ultimately recommend and demand reform at the end of the study.